A méret a lényeg? : Stratégiai dimenziók vizsgálata a szervezet-, illetve piacszerkezet specifikus csoportosítás mentén - Katona, Norbert (Közép-Európai Közlemények, 2016)
During my research I examine the specific characteristic features of strategic management in case of monopolies. As wider scientific interest focuses on strategic motives and behavior of small and medium-sized, or giant multinational, cross-countries enterprises, thus quantitative research conducted in the summer of 2015 among the members of the Hungarian Marketing Association has revealed new results on this field. The study pointed out on one hand pattern of specific market structure and marketing strategic focal points based on domestic, practice-focused marketing specialists, and on the other hand it gave us the opportunity to explore further specific strategic directions and actions along organization dimensions, as well. This paper – reflecting to wider organization dimensions, such as corporate headcount, operation range and main activities of economic organizations – has confirmed the statistically verifiable relationship in connection with strategic patterns of market-leading companies. Outcomes put the focus on stakeholder management and gave distinctive role of strategic future orientation, characterized both tasks as distinctive indicators of strategic operation conducted by monopolies.